(untitled) (Physical Education, Health and Social Sciences, 2025)
This paper applies detailed case studies to the analysis of safety management methods within the DHA business segment of Lahore. It explores the effectiveness of multiple safety processes and identifies their influence on construction risk management, compliance with defined regulations, and occupational health & safety. The report provides practical suggestions to policy-makers, business owners, and the safety managers through highlighting the best practices and frequent challenges. These outcomes would aim at enhancing safety management practices across the region by increasing safety standards and enhancing risk-reducing strategies. The questionnaire was distributed to professionals who work in the construction sector of Lahore, and the findings revealed that the present condition of the on-site safety management practices is rated as a poor one. The report also highlights the need to enhance and implement safety measures. Findings indicate that government agencies and building companies often consider the existing limitations only as a formal means of governmental control, focusing more on maximization of profits rather than the safety of persons. This is to underline how much is needed to make changes so that the safety procedures are observed and given highest priority.